Aqueous Extracts of Lemon Basil Straw as Chemical Stimulator for Gray Oyster Mushroom Cultivation - Pragatsawat Chanprapai; Thanaporn Wichai; Sarintip Sooksai; Sajee Noitang; Weradaj Sukaead; Winatta Sakdasri; Ruengwit Sawangkeaw (My University, 2022)
To reduce the burning of lemon basil straw (LBS)—the byproduct of basil seed production—we propose utilizing LBS as a replacement substrate for mushroom cultivation. LBS can stimulate both mycelial growth and percentage biological efficiency; however, the rigidity of this material limits particle size reduction. In this work, aqueous extractions were facilely performed without using either hazardous chemicals or complex procedures to valorize LBS as a stimulator for gray oyster mushroom cultivation. An aqueous extraction at solid-to-liquid of 50 g/L was employed. The macerated-LBS and decocted-LBS extracts were tested for mycelial growth in potato dextrose agar and sorghum grains. Following this, both aqueous extracts were applied as a wetting agent in cylindrical baglog cultivation to estimate mycelial growth, biological efficiency, and productivity. It was found that LBS extracts insignificantly enhanced the mycelia growth rate on all media, while the diluted LBS (1:1 v/v) extracts improved 1.5-fold of percentage biological efficiency. Gas chromatograph-mass spectrometer results indicated 9-octadecaenamide is a major component in LBS aqueous extract. Results demonstrated that the LBS extract is a good stimulator for the production of Pleurotus mushroom.
Keywords: Aqueous extract; Fungal Biology and Applications